2009
DOI: 10.1051/0004-6361/200810881
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the properties of Lyman-αemitters from redshiftsz~ 3 toz ~ 2

Abstract: Context. Narrow-band surveys to detect Lyα emitters are powerful tools for identifying high, and very high, redshift galaxies. Although samples are increasing at redshifts z = 3−6, the nature of these galaxies is still poorly known. The number of galaxies detected at redshifts below z ∼ 3 are also small. Aims. We study the properties of z = 2.25 Lyα emitters and compare them with those of z > 3 Lyα emitters.Methods. We present narrow-band imaging made with the MPG/ESO 2.2m telescope and the WFI (Wide Field Ima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
237
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 155 publications
(265 citation statements)
references
References 76 publications
24
237
4
Order By: Relevance
“…While low EW Lyα,0 are detected for sources at all redshifts, increasingly larger EW Lyα,0 are measured for sources from samples at higher redshifts. These results are in accordance with the results of Stark et al (2010) who found a similar trend for LBGs with Lyα at z = 3-6, and with the similar findings of Nilsson et al (2009) studying LAEs at lower redshifts (z = 2-3). The speculation is that the change in EW distributions with redshift is the result of increased dust content in LAEs at lower redshifts, but this is yet to be confirmed.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…While low EW Lyα,0 are detected for sources at all redshifts, increasingly larger EW Lyα,0 are measured for sources from samples at higher redshifts. These results are in accordance with the results of Stark et al (2010) who found a similar trend for LBGs with Lyα at z = 3-6, and with the similar findings of Nilsson et al (2009) studying LAEs at lower redshifts (z = 2-3). The speculation is that the change in EW distributions with redshift is the result of increased dust content in LAEs at lower redshifts, but this is yet to be confirmed.…”
Section: Resultssupporting
confidence: 93%
“…Several authors (Shapley et al 2003;Stark et al 2010) have noted an anti-correlation between UV luminosity and EW. This has been refuted by Nilsson et al (2009) who argued that the lack of luminous sources with high EWs may be due to the fact that luminous sources and sources with high EWs are both rare, and that this parameter space has been poorly represented in current flux-limited surveys. Kornei et al (2010) found only a marginal correlation between the EWs and UV luminosities for a large sample of LBGs at z ∼ 3, with M UV < −20.…”
Section: Equivalent Width and Redshift Distributionmentioning
confidence: 99%
“…The Lyα line is predicted to be the dominant spectral signature in young galaxies (Charlot & Fall 1993;Schaerer 2003), and combined with its rest-frame wavelength in the UV, one obtains a very efficient tool for detecting galaxies at 2 < z < 7 in the optical window from ground-based telescopes. Therefore, this potential has often been used to assemble large samples of star-forming galaxies at high redshift (e.g., Gronwall et al 2007;Nilsson et al 2009;Ouchi et al 2010;Hayes et al 2010;Cassata et al 2011;Kashikawa et al 2011). Lyα-based Figure 13 and Tables 1 and 2 are available in electronic form at http://www.aanda.org…”
Section: Introductionmentioning
confidence: 99%
“…For galaxies above redshift two, it is thus crucial to have detections of the galaxies in the near-and mid-IR, corresponding to restframe optical and near-IR wavelengths. Few Lyα emitters have been detected in these wavelength regimes, with only a handful to date at z ∼ 3 (Lai et al 2008), and at z = 4−6 A&A 529, A9 (2011) Nilsson et al (2009a) sample (first lines; divided into the originally published sample and the C-list, or "unlikely" candidates from that paper), divided into the total sample, the sample without GALEX and AGN detections, and the GALEX only, AGN only and combined GALEX and AGN detected LAEs. The "unlikely" candidates were not analysed for AGN and GALEX detections prior to spectroscopic confirmation.…”
Section: Introductionmentioning
confidence: 99%